Social space, leisure time and changing youth cultures in Boğaziçi University since the 70s - Şenoğuz, Hatice Pınar. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
The aim of the thesis is to contribute to the discussions on the current neo-liberal restructuring of higher education in Turkish context. The neo-liberal restructuring not only implies the institutional changes, but it also transforms the social space and the social relations of everyday life. It could be argued that the current discussions concerning the restructuring of higher education remain limited, as they do not tend to conceptualize the implications of such transformation to the everyday life of the students. As universities become more commercial, dominant forms of sociality and lifestyles also change. The inquiry of changing youth cultures could illustrate how the emergent forms of sociality and lifestyles lead the students to adapt themselves to new relations of power and control. My principal concern is to trace the changing cultural representations of youth, leisure and space in Boğaziçi University since the 1970s. I compare the 1970s generation and the generation of 1990s in order to understand how the cultural representations give way to emergent forms of sociality and lifestyles in different decades. In the thesis, I argue that the aesthetic and cultural processes such as cultural fragmentation and aestheticization of everyday life are influential in shaping the youth cultures since the 1970s. Although the youth cultures of the 1970s display the early emergence of a consumerist culture, they are also marked with a political discourse that underlined the class identities and the nationalistic and developmentalist concerns in line with the anti-imperialist struggle. Thus, the youth cultures of the 1970s also constituted a counter-cultural tendency, opposing the individualistic culture in the campus space. On the contrary, the youth cultures of the 1990s point to the fact that social identities become more fluid and culture got fragmented. They are marked by the emergent lifestyles associated with leisure and consumption activities. The thesis elaborates on the aesthetic and cultural processes embedded in various uses of space and the concomitant constitution of youth identities as well. It is demonstrated that the campus space increasingly takes on an iconographic character in the 1990s and turns out nearly a commodity which is to be rented and marketized as the image of the university. These processes also afford visibility to companies and to the cultural consumption styles that place an emphasis upon the bodily display of tastes. As the space turns out to a medium of exchange of looks, emergent spaces of public display not only expose the students to the display of new tastes, but also afford pleasure and satisfaction derived from looking. The thesis demonstrates that these processes could also inform new forms of symbolic resistance.
Keywords: Youth -- Turkey -- Social conditions.; Youth -- Turkey -- Conduct of life.; Young adults -- Education (Higher) -- Turkey.